1995
DOI: 10.1007/bf00004347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin, p-chlorophenylalanine, and ?-methylparatyrosine on plasma gonadotropin level and ovarian activity in the catfish, Heteropneustes fossilis: A study correlating changes in hypothalamic monoamines

Abstract: The effects of (ip, 10 injections over 20 days) of melatonin (75 μg 100 g(-1) BW), the serotonin (5-HT)-synthesis blocker, para-cholorophenylalanine (p-CPA, 10 mg 100g(-1 BW)) and the catecholamine-synthesis blocker, α-methylparatyrosine (α-MPT, 10 mg 100 g(-1) BW) on gonadotropin (GTH) secretion and ovarian activity were studied in (Heteropneustes fossilis) during late preparatory to early prespawning (April-May). The treatments resulted in significant reductions of plasma GTH and estradiol-17β levels, the go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The mechanism by which exogenous melatonin exerts its regulatory actions on the gonads is not clearly known. There is a possibility that melatonin interacts with the brain-pituitary-gonadal axis (Amano et al 2000), or with one or more of a variety of peripheral and/or central sites, including the serotonergic system of the hypothalamus (Senthilkumaran and Joy 1995), brain (Khan and Thomas 1996), pituitary gland (Khan and Thomas 1996;Gaildrat and Falcon 2000), and also directly on the gonads (Amano et al 2000). Obviously, evidence from further study is essential before ruling out any such possibilities in a hitherto unstudied fish like carp.…”
Section: Dose-and Duration-dependent Influences Of Exogenous Melatonimentioning
confidence: 92%
See 1 more Smart Citation
“…The mechanism by which exogenous melatonin exerts its regulatory actions on the gonads is not clearly known. There is a possibility that melatonin interacts with the brain-pituitary-gonadal axis (Amano et al 2000), or with one or more of a variety of peripheral and/or central sites, including the serotonergic system of the hypothalamus (Senthilkumaran and Joy 1995), brain (Khan and Thomas 1996), pituitary gland (Khan and Thomas 1996;Gaildrat and Falcon 2000), and also directly on the gonads (Amano et al 2000). Obviously, evidence from further study is essential before ruling out any such possibilities in a hitherto unstudied fish like carp.…”
Section: Dose-and Duration-dependent Influences Of Exogenous Melatonimentioning
confidence: 92%
“…We also reported ) that pineal functions in carp were stimulated following exposure to continuous illumination (LL), but inhibited under the influence of continuous darkness (DD). A study on H. fossilis indicated the importance of the serotonergic system in the action of melatonin on the pituitary-gonadal axis (Senthilkumaran and Joy 1995). Thus, further studies on the possible role of the pineal gland and/or melatonin in the regulation of the hypothalamus-pituitary-gonadal axis in carp would be worthwhile.…”
Section: Importance Of Photoperiods In the Regulation Of Ovarian Actimentioning
confidence: 99%
“…Previous studies in teleosts have shown that hypothalamic CA activity is influenced by the circulating levels of E 2 [21,22,42,43]. In H. fossilis, ovarian E 2 varies seasonally and exerts feedback effects on hypothalamic CA activity depending on the season and concentration of the steroid administered [20,23,31,32]. These studies indicate that E 2 interacts with the hypothalamic CA system at different enzyme-catalyzed metabolic steps (DbH, PNMT and COMT) to alter its activity, which, in turn, regulates LH secretion [44].…”
Section: Discussionmentioning
confidence: 99%
“…Gonadectomy inhibited mRNA levels in TH neurons and E 2 replacement partially reversed the effect [30]. Senthilkumaran and Joy [31] showed that a-MPT inhibited differentially CA content and turnover depending on the reproductive phase. The changes in CA activities following the a-MPT treatment have impaired the functioning of the neuroendocrine-gonadal axis and decreased spawning activity [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation